A novel approach for synthesizing silver nanoparticles with antibacterial and cytotoxic activities using the leaf extract of hydroponically grown Moringa oleifera - Anush Aghajanyan; Marina Timotina; Tatevik Manutsyan; Ani Harutyunyan; Mikayel Ginovyan; Robin Schubert; Sofiya Aydinyan; Karen Trchounian; Lilit Gabrielyan; Liana Gabrielyan (Scientific Reports)
Abstract Novel approaches for producing silver nanoparticles (Ag-NPs), which are widely used in biomedicine, biotechnology, and agriculture, are of considerable importance. This study highlights a simple and cost-effective biological method for the synthesis of Ag-NPs using the leaf extract of the hydroponically cultivated Moringa oleifera (MOAg-NPs), alongside the analysis of the biosynthesized NPs. One of the advantages of hydroponic cultivation over traditional soil-based methods is that plants are cleaner since they are not in contact with soil and can be cultivated with fewer chemical inputs. For characterization of the biosynthesized MOAg-NPs various methods have been used, such as UV-visible (UV-Vis) spectroscopy, transmission electron microscopy (TEM), X-Ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. UV-Vis analysis revealed a prominent peak at 465 nm, indicating the synthesis of MOAg-NPs. TEM analysis demonstrated a spherical shape of MOAg-NPs with an average diameter of 10.0 ± 6.0 nm. The XRD pattern displayed Ag peaks at 2θ values corresponding to (111), (200), (220) and (311) reflections. The antibacterial efficacy of MOAg-NPs was assessed against Gram-positive (Enterococcus hirae, Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli), revealing their antibacterial potential at low concentrations. The general inhibitory mechanism of MOAg-NPs focuses on the energy-dependent total and N, N’-dicyclohexylcarbodiimide (DCCD)-sensitive H+-fluxes across the bacterial membrane. Moreover, the application of MOAg-NPs resulted in substantial inhibition of HeLa cells growth. Thus, Ag-NPs synthesized using hydroponically grown M. oleifera leaf extract exhibited cytotoxicity against cancer cells and antibacterial properties, highlighting their potential use in biomedicine.